A new species of Gurania (Cucurbitaceae) from Northeastern Brazil - Gomes-Costa, Géssica A.; Barbosa, Maria Regina De V. (Phytotaxa, 2016)
During analysis of herbarium collections for a taxonomic review of the Brazilian species of Gurania from the Atlantic forest, one new species was discovered. The new species is known only from the state of Bahia and honors Dr. Michael H. Nee. A description, illustrations, and photos of Gurania neei are presented along with comments on its similarities and differences with related species.